Synthesis Mechanism of Nano BaTiO3 Particles at Low Temperature by Molten Salt Method - Hyun Lee, Chang; Soon Shin, Hyo; Hun Yeo, Dong; Hyun Ha, Gook; Nahm, Sahn (Asian Journal of Chemistry, 2014)
Using the molten salt method, nano BaTiO3 can be synthesized at 150 ºC and atmospheric pressure for thick film application. It was reported that this is a result of the moisture in the air being absorbed in the salt. However, the precise mechanism of the nano BaTiO3 particle synthesis at such low temperature, air and atmospheric pressure has not been presented yet. Therefore, by observing the intermediate stage of the synthesis through varying the synthesis time at the low temperature of 150 ºC, experimental results regarding the synthesis process were obtained. Experimental results showed that BaTiO3 powder below 20 nm was synthesized when synthesis was conducted over 10 h using the molten salt method employing KOH-KCl mixed salt at 150 ºC. By varying the synthesis time from 1 to 10 h, the microstructure and XRD phase analysis results revealed that the mixed salt does not melt overall and the moisture in the air is absorbed in the salt to form an oxalate coating layer. The mechanism where nano BaTiO3 is synthesized through the dissolution and reaction of the base materials BaCO3 and TiO2 in the coating layer is discussed here.